Striving for Inclusive Excellence: A Personal Journey - Bajor, William; Sax, Christina; Dennis, Michelle; John, Shino; Mayol, Ana-Rita (American Journal of Management, 2020)
This work explores the construct of inclusive excellence, as applied to instances of ageism in higher education settings. Impacts of inclusive excellence pertaining to students, faculty, staff, alumni, institutions of higher education, and the community are explored. An analysis of two vignettes is provided to illustrate aspects and impacts of ageism in higher education. Inclusive excellence is discussed as a framework from which to evaluate the equity of treatment. Recommendations for future planning are provided.